The Implementation of Video Blog (Vlog) as a Teaching Media in Speaking Skill - Dani Fitria Brilianti; Hana Yulinda Fithriyani (STKIP Singkawang, 2020)
The use of appropriate media in the learning and teaching process especially in teaching speaking is quite important for the lecturers to have students' the best result. The video blog (Vlog) is one of the media that commonly used by lecturers in teaching speaking English to gain students' motivation in speaking. The main aim of this study is to investigate the lecturer's strategy in implementing video blog as a media in teaching speaking. Besides, it is also to identify the difficulties of vlog implementation in teaching speaking. To achieve the objectives, the descriptive qualitative approach in the form of a case study was chosen as the method of the research. Observation and interview were collected as the data to the class 2A, a second-semester student of Computer Engineering Students of Politeknik Harapan Bersama, Tegal, Indonesia. The data from classroom observation were obtained from activity portrait, video recording, students and lecturers' notes, and interview during observation. The data analysis presented by using descriptive explanation, and the data result from lecturers' interview were summarized by using the table and described based on the phenomenon that found during the observation. The finding of data showed that the lecturer applied task-based learning to implement vlog in speaking skill. The lecturers did not only show the vlog to the students in teaching speaking as the media but also asked them to make it by their selves and uploaded it to the YouTube Channel as the new references of English vlog. Lecturers began the learning and teaching process with pre tasks: introduction, review to the previous material; then continued to the main tasks: showing the model/media, giving task, and discussion; and closed by the post-task: evaluation and feedback. Moreover, the difficulties faced by the lecturers in implementing vlog in teaching speaking were a distinct range of students' English scores especially in speaking, the improper gadget that owns by the students’ to make the video blog, and lack of students’ creativity in building the video blog content to make it interesting to be watched. In line with the previous studies, which stated that video blog is interesting and it can improve students' speaking skill effectively.